2022
DOI: 10.1007/s00432-022-04511-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of mistletoe prescriptions in clinical studies

Abstract: Purpose Mistletoe treatment is discussed controversial as a complementary treatment for cancer patients. Aim of this systematic analysis is to assess the concept of mistletoe treatment in the clinical studies with respect to indication, type of mistletoe preparation, treatment schedule, aim of treatment, and assessment of treatment results. Methods In the period from August to December 2020, the following databases were systematically searched: Medline, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…These compounds are known to produce dose-dependent hypertension or hypotension, bradycardia and increased uterine and gastrointestinal motility. However, the published literature on the human toxicity of mistletoe-containing products indicates that the majority of patients evidenced good tolerability and remained asymptomatic, with no reported deaths [ 111 , 129 , 130 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 ].…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are known to produce dose-dependent hypertension or hypotension, bradycardia and increased uterine and gastrointestinal motility. However, the published literature on the human toxicity of mistletoe-containing products indicates that the majority of patients evidenced good tolerability and remained asymptomatic, with no reported deaths [ 111 , 129 , 130 , 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and complex alterations by epigenetic modifications of tumor gene expression profiles contribute to the development of resistance to treatment [154]. European mistletoe (Viscum album L) are commonly employed in combination with traditional cancer treatments or as a standalone alternative therapy for individuals diagnosed with cancer [155]. Recent research has revealed potential implications of mistletoe in the prognosis of individuals diagnosed with colorectal or pancreatic carcinomas [156,157].…”
Section: Natural Compound In Clinical Trialmentioning
confidence: 99%
“…European mistletoe (Viscum album) is commonly employed in combination with traditional cancer treatments or as a stand-alone alternative therapy for individuals diagnosed with cancer [230]. Mistletoe extracts include lectins, viscotoxins, flavonoids, and membrane lipids.…”
Section: Herbal Medicines In Vitro Assay To Improve Pdac Therapeutic ...mentioning
confidence: 99%